Maximum principle for stochastic control in continuous time with hard end constraints - Atle Seierstad (University of Oslo, Department of Economics, 2002)
A maximum principle is proved for certain problems of continuous time stochastic control with hard end constraints, (end constraints satis_ed a.s.) After establishing a general theorem, the results are applied to problems where the state equation (di_erential equation) changes at certain stochastic points in time, and to piecewise continuous stochastic problems (including piecewise deterministic problems).
Keywords: C61; 330; Piecewise deterministic; hard end constraints; Stochastischer Prozess; Theorie